Development and validation of DNA metabarcoding COI primers for aquatic invertebrates using the R package "PrimerMiner" - Elbrecht,Vasco; Leese,Florian (PeerJ Preprints, 2016)
1) DNA metabarcoding is a powerful tool to assess biodiversity by amplifying and sequencing a standardized gene marker region. However, typically used barcoding genes, such as the cytochrome c oxidase subunit I (COI) region for animals, are highly variable. Thus, different taxa in communities under study are often not amplified equally well and some might even remain undetected due to primer bias. To reduce these problems, optimized metabarcoding primers for the typical communities found in certain geographic regions- and/or ecosystems are necessary. 2) We developed the R package PrimerMiner, which batch downloads DNA barcode gene sequences from BOLD and NCBI databases for specified target taxonomic groups and then applies sequence clustering to reduce biases introduced by the different number of available sequences per species. We downloaded COI data for the 15 most relevant freshwater invertebrate groups for stream ecosystem assessment and developed four primer sets with high base degeneracy based on that. Primer performance was tested by sequencing ten mock community samples each consisting of 52 freshwater invertebrate taxa. Additionally, we used PrimerMiner to evaluate the developed primers against other metabarcoding primers in silico. 3) The developed primers varied in amplification efficiency and the amount of detected taxa, yet all retrieved more taxa than standard Folmer barcoding primers. Additionally, the BF/BR primers amplified taxa very consistently, with the BF2+BR2 and BF2+BR1 primer combinations showing better amplification than a previously tested ribosomal marker (16S). Except for the BF1+BR1 primers all BF/BR primers combinations detected all 42 insect taxa present in the mock community samples. In silico evaluation of the developed primers demonstrates their suitability for metabarcoding of non-aquatic insect samples. 4) With PrimerMiner we provide a useful tool to obtain relevant sequence data for targeted primer development and evaluation. Our sequence datasets generated with the newly developed metabarcoding primers demonstrate that the design of optimized primers with high base degeneracy is superior to classical markers and enables us to detect almost 100% of animal taxa present in a sample using the standard COI barcoding gene. Therefore, the PrimerMiner package and the developed primers are useful beyond biodiversity assessment in aquatic ecosystems.
Keywords: Primer Development; DNA metabarcoding; ecosystem assessment; data mining; primer bias; in silico PCR